2023
DOI: 10.1159/000527552
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Parenteral Nutrition Is Feasible and Safe in Very Low Birth Weight Preterm Infants: A Randomized Trial

Abstract: <b><i>Objective:</i></b> The objective of this study was to determine the feasibility and safety of enhanced early (PN) (early initiation of intralipids and faster advancement of glucose infusion rate) during the first week of life for very low birth weight (VLBW) preterm infants. <b><i>Methods:</i></b> 90 VLBW preterm infants (&#x3c;32 weeks gestational age at birth) admitted to the University of Minnesota Masonic Children’s Hospital between August 2017 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…A mixed-cohort study showed that fortified human milk resulted in higher energy, fat, and carbohydrate intakes but a lower protein-to-energy ratio [ 21 ]. Similarly, enhanced parenteral nutrition in the very-low birth weight preterm infants resulted in increased energy intake and was feasible with no side effects [ 44 ]. In our study, the weight gain velocity was highest in the very preterm subgroup, obviously revealing an increased need for protein intake, which could not be achieved in this subcohort.…”
Section: Discussionmentioning
confidence: 99%
“…A mixed-cohort study showed that fortified human milk resulted in higher energy, fat, and carbohydrate intakes but a lower protein-to-energy ratio [ 21 ]. Similarly, enhanced parenteral nutrition in the very-low birth weight preterm infants resulted in increased energy intake and was feasible with no side effects [ 44 ]. In our study, the weight gain velocity was highest in the very preterm subgroup, obviously revealing an increased need for protein intake, which could not be achieved in this subcohort.…”
Section: Discussionmentioning
confidence: 99%
“…Nagel et al studied the feasibility and safety of enhanced early PN (early initiation of intravenous lipid emulsions and faster advancement of glucose infusion rate) during the first week of life for VLBW preterm infants. 8 90 VLBW preterm infants (<32 weeks gestational age at birth), stratified by gestational age and randomised to enhanced nutrition versus a standard PN protocol. Enrolled infants were stratified by gestational age groups and randomised to either the enhanced nutrition protocol (intervention group) or the standard PN protocol (standard group).…”
Section: Introductionmentioning
confidence: 99%